2017
DOI: 10.3389/fphys.2017.00715
|View full text |Cite
|
Sign up to set email alerts
|

Syngeneic B16F10 Melanoma Causes Cachexia and Impaired Skeletal Muscle Strength and Locomotor Activity in Mice

Abstract: Muscle wasting has been emerging as one of the principal components of cancer cachexia, leading to progressive impairment of work capacity. Despite early stages melanomas rarely promotes weight loss, the appearance of metastatic and/or solid tumor melanoma can leads to cachexia development. Here, we investigated the B16F10 tumor-induced cachexia and its contribution to muscle strength and locomotor-like activity impairment. C57BL/6 mice were subcutaneously injected with 5 × 104 B16F10 melanoma cells or PBS as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 36 publications
4
31
2
3
Order By: Relevance
“…However, in our study, the levels of gene expression for pro‐inflammatory cytokines in the spleen were inconsistent, since gene expression of TNF‐α and NF‐κB was markedly decreased in tumor‐bearing mice and IL‐6 mRNA levels were not changed in these animals. In contrast to our findings, Voltarelli et al () found elevated serum levels of TNF‐α and IL‐6 in C57Bl/6J mice subcutaneously injected with B16‐F10 melanoma cells; however, IL‐1β levels were not included in their study. Observed differences in the peripheral levels of the pro‐inflammatory cytokines TNF‐α and IL‐6 in ours and Voltarelli et al () studies may be a consequence of differences in the stage of melanoma.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, in our study, the levels of gene expression for pro‐inflammatory cytokines in the spleen were inconsistent, since gene expression of TNF‐α and NF‐κB was markedly decreased in tumor‐bearing mice and IL‐6 mRNA levels were not changed in these animals. In contrast to our findings, Voltarelli et al () found elevated serum levels of TNF‐α and IL‐6 in C57Bl/6J mice subcutaneously injected with B16‐F10 melanoma cells; however, IL‐1β levels were not included in their study. Observed differences in the peripheral levels of the pro‐inflammatory cytokines TNF‐α and IL‐6 in ours and Voltarelli et al () studies may be a consequence of differences in the stage of melanoma.…”
Section: Discussioncontrasting
confidence: 99%
“…The cachexia index considers the body weight gain of control mice and the tumor mass in tumor‐bearing mice, according to the following the equation:%Loss of body mass=IBM-FBM+(MT)+GMC×100/false(IBM+GMCfalse).where: IBM is the initial body mass of the tumor‐bearing mice, FBM is the final body mass of the tumor‐bearing mice, MT is the tumor mass, and GMC is the mean mass gain of the control group. The animals were considered cachectic when the loss of body mass was >5% (Martins et al, ; Voltarelli et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Cancer cachexia is a paraneoplastic syndrome characterized by body weight loss, muscle wasting, adipose tissue atrophy and inflammation 44 , in which muscle wasting has emerged as a principal component of cancer cachexia, leading to progressive impairment of work capacity 45 . Here, we showed that despite the significant decrease of body weight gain after oral treatment with crotamine, no significant body weight loss or decrease in skeletal muscle, brain, kidney or heart weight was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The others (20) were similarly inoculated with 3.5x10 5 LLC tumor cells (suspended in 200 μ l of Dulbecco´s modified Eagle´s medium). Next, the animals were transferred to sterile cages and kept, under the conditions described above, for a period of 28 days, when cachexia symptoms could be verified (23,24). Stool samples were collected daily, from each mouse, until day 28.…”
Section: Cachexia Induction In C57bl/6 Mice and Collection Of Stool Smentioning
confidence: 99%
“…This information was used to calculate the Cachexia Index (CI) in the LLCinoculated animals, following the methodology described in 24. According to these calculations, 8 animals showed CI values ≥ 5, indicating full development of cachexia (24). These animals were further evaluated for their cachectic condition by histometric characterization of muscle (gastrocnemius) and adipose (epididymal) tissues (25), as well as by measuring the expression of molecular markers for muscular atrophy (Atrogin) and inflammation (IL6 receptor), by real-time quantitative PCR (qPCR) (see 26,27,28), for details).…”
Section: Assessment Of Cachexia Progressionmentioning
confidence: 99%